Online Arbitration in E-Commerce Dispute Resolution During the Pandemic Covid-19 - Mohammad Ghozali; Budi Ispriyarso (Magister of Law, Faculty of Law, Universitas Islam Sultan Agung, 2021)
The Covid-19 pandemic has made online buying and selling activities increasing. E-commerce is full of risks, especially because the consumers have the obligation to make any advance payment while they cannot see the condition or quality of the goods they ordered. With the emergence of business disputes that occur both online and offline, and with the development of increasingly sophisticated technology, it is expected that the settlement of business disputes can be resolved online. The purpose of this study was to analyze the settlement of legal disputes against online buying and selling transactions during the Covid-19 pandemic which was carried out through online arbitration. The research method used was the normative juridical method, which was a method that seeks to analyze dispute resolution carried out through online arbitration which was then linked to the provisions of laws and regulations. The process of conducting online arbitration is by using the internet as media. The room for communication is more like a chat room based on real-time audio-visual streaming. With the application to communicate, the parties can convey their data, facts, information, or responses through this platform. Legal sanctions against online buying and selling transactions that do not match the order are regulated in two general rules (Lex Generalis) and special rules (Lex Specialist).Keywords: E-Commerce; Covid-19, Online Arbitration; Legal Sanctions.